The Divide Between Vocational and Academic Education and How We Might Be Able to Repair the Rift. - Sych, Susan Margaret (Journal of the Canadian Association for Curriculum Studies, 2016)
The following article provides a historical perspective to the notion there is a divide between academic and vocational education and training (VET). The author explores the biases held by parents, teachers, administrators and policy-makers toward VET, and provides explanations of why these views might be held. Even though positive changes have been made in promoting VET there still remains an undercurrent of negative discourse. The autobiographical approach of the article provides the writer with the means to challenge the negative perspectives, and presents a personal view into how VET might be vindicated from denigrating attitudes.